P2.166 The Effectiveness of SMS Texts For Reminding Patients at High Risk of STIs and HIV to Return For Testing. (13th July 2013) - Brook, G; Burton, J; McSorley, J; Murphy, S
Abstract : Background: Patients attending sexual health services for STI/HIV testing may be at continuing risk of infection acquisition or may be within a window period for testing and may be advised to return for retesting at various intervals. Technology such as SMS texting facilitates the sending of reminders. Objectives: To measure the impact of the SMS text reminders on the re-attendance rates of patients who require repeat testing. Methods: Re-attendance rates were measured for patients listed for routine SMS text reminders (September to November 2012) and a control group with the same risk factors from a period when text reminders were not routinely used (September to November 2011). Re-attendance was counted if it was within 2 months of the text or, for the control group, within 3 months of the end of the previous episode of care. Results: Following the introduction of SMS text reminders, the re-attendance rate was 41% (84/207) in the text group compared to 28% (47/169) in the control group to P < 0.001. The risk groups most likely to respond to texting were those patients in the window period for HIV (10/33, 30% vs 4/26.15% P < 0.05), women who had received emergency contraception (25/54.46% vs 15/43, 35% P < 0.05) and MSM not in other risk categories (8/17, 47% vs 2/16, 13% P < 0.05). No differences were observed in the return rate for patients with other risks (recent acute STIs, syphilis, recent viral hepatitis and sex workers). Conclusions: SMS texts sent as reminders to patients at higher risk of STIs and HIV increases the overall re-attendance rate by 13% and was especially effective for MSM, people in the window period for HIV and women who had received emergency contraception. Routine text reminders are an effective, cheap and simple way of ensuring that high-risk patients return for testing.